2010
DOI: 10.1210/jc.2009-1913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex, Race, and Puberty on Cortical Bone and the Functional Muscle Bone Unit in Children, Adolescents, and Young Adults

Abstract: Sex and race were associated with maturation-specific differences in cortical BMD and dimensions that were not fully explained by differences in bone length or muscle. No race or sex differences in the functional muscle bone unit were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
128
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 30 publications
(34 reference statements)
14
128
2
Order By: Relevance
“…Race, sex, and pubertal differences in pQCT measures of cortical bone and muscle area were recently reported in the CHOP reference participants. 1 A subset of 302 reference participants at CHOP enrolled in an ancillary longitudinal study with an additional visit at 12 months, as previously described. 40 The study protocol was approved by the Institutional Review Boards at CHOP and CCHMC.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Race, sex, and pubertal differences in pQCT measures of cortical bone and muscle area were recently reported in the CHOP reference participants. 1 A subset of 302 reference participants at CHOP enrolled in an ancillary longitudinal study with an additional visit at 12 months, as previously described. 40 The study protocol was approved by the Institutional Review Boards at CHOP and CCHMC.…”
Section: Study Participantsmentioning
confidence: 99%
“…pQCT results were compared with reference data generated in more than 700 concurrent healthy participants. 1,[19][20][21] The hypotheses were that glucocorticoid exposure and resolution of secondary hyperparathyroidism after renal transplantation would be associated with declines in trabecular BMD and increases in cortical BMD. 12,22 We also hypothesized that increases in muscle area after renal transplantation would be associated with increases in cortical dimensions.…”
mentioning
confidence: 99%
“…10 African Americans have greater maturation-specific trabecular density and cortical structural strength. 11 Indeed, we recently examined adult bone loci in a multi-ethnic pediatric setting. 12 Using polygenic risk scores, we demonstrated that adult variants are predictive of BMD early in childhood and adolescence; further, we showed that, within the study cohorts and across populations worldwide, the frequency of those alleles associated with increased BMD is systematically …”
Section: Introductionmentioning
confidence: 99%
“…Femur cross-sectional area, but not cortical area, was also greater in these children, even when taking into consideration the significantly longer femurs in blacks vs. whites. Finally, Leonard et al [136] showed that all tibia cortical bone measures, corrected for tibia length, including BMC, BMD, periosteal and endosteal circumferences, and section modulus, were greater in blacks vs. whites [137]. Unlike the Gilsanz et al [136] study, the differences in vertebral cancellous BMD were less apparent by Tanner stage 5 in this study [137].…”
Section: Skeletal Accretionmentioning
confidence: 43%
“…Finally, Leonard et al [136] showed that all tibia cortical bone measures, corrected for tibia length, including BMC, BMD, periosteal and endosteal circumferences, and section modulus, were greater in blacks vs. whites [137]. Unlike the Gilsanz et al [136] study, the differences in vertebral cancellous BMD were less apparent by Tanner stage 5 in this study [137]. Wetzsteon et al [138] showed in younger adolescents (9e12 years of age) that both blacks and Hispanics have greater radius and tibia vBMD, cortical area and bone strength than whites, after correcting for age, sex as well as bone and muscle size.…”
Section: Skeletal Accretionmentioning
confidence: 99%